Beauty and the beak : how science, technology, and a 3D-printed beak rescued a bald eagle - Rose, Deborah Lee; Veltkamp, Jane (Persnickety Press, 2017)
The true story of Beauty the eagle's rescue and rehabilitation. Beauty has been featured on Nat Geo WILD TV's Unlikely Animal Friends, in the National Wildlife Federation's Ranger Rick magazine, and on the National Academy of Engineering (NAE) EngineerGirl website.